Use of Angiotensin Receptor Neprilysin Inhibitor in Patients on Maintenance Hemodialysis with Reduced Cardiac Ejection Fraction, Real-World Experience From a Single Center (Iranian Journal of Kidney Diseases, 2021)
Introduction. Angiotensin receptor neprilysin inhibitor (ARNI) has been recommended by major guidelines as the leading therapy for heart failure with reduced ejection fraction (HFrEF). But little is known about its safety and effectiveness among maintenance hemodialysis patients with HFrEF in real-word practice. Methods. An observational study was conducted among maintenance hemodialysis patients who received ARNI at our dialysis center. Enrollment commenced on June 1, 2018; and follow-up was completed on May 31, 2019. Results. A total of 110 patients included in the study (age: 54.2 ± 14.8 y, 59% males). After 12 months of treatment, the average ARNI daily dose increased from 135 mg to 308 mg. The mean NT-pro- BNP concentration at baseline was 14455 pg/mL and 6435 pg/ mL after 12 months of treatment (P < .001). The left ventricular ejection fraction improved (35.1 vs. 49.8%, P < .001) over the 12 months, while left ventricular end-diastolic diameter, left ventricular mass index, left ventricular end-systolic diameter, and left atrial diameter also changed significantly (167.8 vs. 154.9 g/m, P < .001; 52.2 vs. 51.5 mm, P < .05; 35.9 vs. 36.9 mm, P < .001; 42.2 vs. 40.3 mm, P < .001). Furthermore, we found the quality of life and the NYHA symptom severity class improved significantly (P < .001). Kaplan-Meier analysis indicated that higher dose of ARNI and less vintage of HD were associated with best survival. Conclusion. In our study, ARNI appeared to be safe, relieved heart failure symptoms, and improved the scores of KCCQ physical and social activities in hemodialysis patients in real-world practice.DOI: 10.52547/ijkd.5875